Motivating factors influencing youth smallholder farmers to adopt sweet potato seed technology: A means-end chain approach - Mayanja, Sarah; Kwikiriza, Norman; Mwende, Janet; Okello, Julius; Jagwe, John; Ssekandi, Joseph (International Potato Center, 2023)
Sweet potato, with its nutritional benefits, high yield, and fast maturity, holds great potential for addressing food scarcity in arid areas. However, smallholder farmers in these regions face challenges in preserving sweet potato seed, particularly after prolonged dry spells. Lack of effective storage methods and difficulty in maintaining quality seed impede farmers from fully harnessing the crop’s potential to enhance their food and income security. To address this issue, the Triple S (Sand, Storage, Sprouting) approach was introduced as a root-based technology for preserving sweet potato seed. Despite its availability, farmers have shown inconsistent adoption of this technology. To gain insights into the motivators for adopting or dis-adopting the Triple S, this study employed the laddering technique and interviewed 60 randomly selected male and female youth farmers, categorized as users and non-users of the technology. Interviews revealed the attributes, consequences, and values associated with the technology, uncovering the underlying mental constructs that influence the adoption decisions of young farmers and the values that shape those choices. The findings highlight that personal values such as a healthy life, happiness, social security, achievement of personal goals, and peace of mind drive the adoption of the Triple S. Specifically, only female users mentioned peace of mind as a significant motivator. On the other hand, non-use of the technology was associated with negative values, including perceptions of being unhealthy, unhappy, and ashamed. The study underscores the importance of understanding mental constructs in designing effective strategies for technology uptake and provides policy recommendations to address this matter.